2020
DOI: 10.25165/j.ijabe.20201304.5587
|View full text |Cite
|
Sign up to set email alerts
|

Growing-season soil microbial respiration response to long-term no tillage and spring ridge tillage

Abstract: No tillage (NT) and spring ridge tillage (SRT) are two common applications of conservation tillage. Although conservation tillage is known to exert major control over soil microbial respiration (SMR), the growing-season SMR response to these two applications remains elusive. In order to better understand the influence of conservation tillage practices, this experiment was conducted in an experimental field using NT and SRT for 17 years. In situ measurements of SMR, soil temperature and soil water content (SWC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…The proportion of MOM carbon (types C, F, and I) exceeded that of POM and LF. Limited aeration within microaggregates inhibited microbial activity and was responsible for the high values of MOM carbon proportion [37,38]. An increase in salt levels with cultivation years of greenhouse enhanced organo-mineral associations within microaggregates [9,39,40].…”
Section: Carbon Density Fraction Distribution In Aggregates In Respon...mentioning
confidence: 99%
“…The proportion of MOM carbon (types C, F, and I) exceeded that of POM and LF. Limited aeration within microaggregates inhibited microbial activity and was responsible for the high values of MOM carbon proportion [37,38]. An increase in salt levels with cultivation years of greenhouse enhanced organo-mineral associations within microaggregates [9,39,40].…”
Section: Carbon Density Fraction Distribution In Aggregates In Respon...mentioning
confidence: 99%
“…Conservation tillage generally promotes higher microbial activity, as the accumulation of organic residues in the topsoil and minimal soil disturbance increase its carbon concentration, which correlates positively with microbial biomass and microbial communities. An increase in soil organic carbon (OC) under these conditions creates a stable bacterial network and greater microbial diversity, raising enzyme activity levels and increasing microbial metabolic activity under conservation agriculture compared to conventional management [4,5]. In addition, Panettieri et al [6] have shown that non-tillage increases the quantity of soil fungi over bacteria, and Li et al [7] have reported a significant increase in the microbial population, fungal biomass, and bacterial diversity with non-tillage compared to conventional tillage.…”
Section: Introductionmentioning
confidence: 99%